2021
DOI: 10.3389/fpubh.2021.625779
|View full text |Cite
|
Sign up to set email alerts
|

Post-partum Hospital Stay and Mothers' Choices on Breastfeeding and Vaccines: A Chance We Should Not Miss

Abstract: Parents' education and knowledge regarding major topics of children's health, such as nutrition and vaccines, have a paramount role. However, breastfeeding rates in first year of life are lower than recommended, and vaccine hesitancy is progressively spreading. To reverse this harmful trend, healthcare professionals are challenged to promote correct health information. This study aimed to assess newly mothers' knowledge of breastfeeding and vaccinations, and education received on both topics during hospital st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…While allergic risks are normally assessed during initial encounters, ECAP is addressed only implicitly as part of general advice on nutrition, hygiene, and smoking. Morniroli et al ( 2021 ) concluded that mothers need a thorough knowledge on prevention topics, as otherwise benefits of breastfeeding and vaccines may be underestimated. This may be the case for ECAP as well, because parents may underestimate the potential of prevention of advice on ECAP when it only resonates in other areas such as nutrition, hygiene, and living environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While allergic risks are normally assessed during initial encounters, ECAP is addressed only implicitly as part of general advice on nutrition, hygiene, and smoking. Morniroli et al ( 2021 ) concluded that mothers need a thorough knowledge on prevention topics, as otherwise benefits of breastfeeding and vaccines may be underestimated. This may be the case for ECAP as well, because parents may underestimate the potential of prevention of advice on ECAP when it only resonates in other areas such as nutrition, hygiene, and living environment.…”
Section: Discussionmentioning
confidence: 99%
“…Allergic diseases, including allergic rhinitis, food allergy, asthma, and atopic dermatitis are a major public health concern ( Asher et al, 2006 ; Bergmann et al, 2016 ; Peters et al, 2017 ). Preventive measures are crucial for optimizing health outcomes across the lifespan and may reduce the risk of allergies, particularly when addressed in young children ( Caffarelli et al, 2018 ; Morniroli et al, 2021 ). However, guidelines and recommendations regarding early childhood allergy prevention (ECAP) are complex and keep changing.…”
mentioning
confidence: 99%
“…The in-hospital immediate postpartum period was considered by Gao et al [ 25 ] a significant time for healthcare workers to give professional support to mothers for establishing exclusive breastfeeding. Indeed, the post-partum hospital stay offers a valuable “window of opportunity” for parental education [ 26 , 27 ], since, during this short period of time, mothers are generally eager to learn as much as they can about newborn care. However, brief postpartum hospital stays (at our hospital, the mean hospital stay for mothers of healthy newborns varies from 2 or 3 to 5 days, according to mode of delivery, vaginal vs. cesarean section, respectively) often leave insufficient time for healthcare professionals to address a new mother’s learning needs effectively.…”
Section: Discussionmentioning
confidence: 99%